Strengthening Vocational Competencies and Quality Culture in Small-Scale Food Enterprises: A Case Study of Tofu Production Improvement Using the Six Sigma Approach - Ramadhania, Firanti (Journal of Supply Chain and Entrepreneurship, 2025)
Background: Small-scale food enterprises in Indonesia often rely on inherited production habits rather than structured vocational knowledge, causing inconsistent quality and limited competitiveness. The tofu industry, particularly in rural areas such as Situbondo, faces challenges related to worker discipline, hygiene culture, and process control. These issues highlight the need for strengthening vocational competencies and embedding a quality-oriented work culture within microenterprises. Aims: This study aims to examine how the introduction of a structured improvement framework can enhance workforce behavior, production discipline, and overall quality culture in a rural tofu-processing enterprise. The article reframes technical findings into insights that support vocational learning, organizational development, and local MSME empowerment. Methods: Using a case-study design, the research applies the Six Sigma DMAIC framework to analyze quality issues at UD Barokah. Data were collected through direct observation, interviews with workers and owners, and defect recording across 20 sampling periods. The study investigates four key defect categories—aroma, taste, color, and size—and identifies behavioral, environmental, and procedural factors that influence production performance. Results: Findings show a high defect rate represented by a DPMO value of 269,000 and a sigma level of 2.11, indicating unstable processes and weak adherence to vocational standards of hygiene, measurement accuracy, and equipment maintenance. Dominant defects include discoloration and contamination, which stem from inconsistent worker practices, inadequate sanitation routines, and the absence of standardized procedures. Conclusion: The study demonstrates that technical improvement tools can function as pedagogical instruments that reshape work behavior, reinforce vocational competencies, and cultivate a sustainable quality culture in micro-scale food enterprises. Beyond reducing product defects, the Six Sigma approach encourages structured learning, strengthens accountability among workers, and promotes a culture of cleanliness and precision that is essential for rural MSME development. Embedding such quality-oriented practices is crucial for empowering local enterprises, enhancing consumer trust, and supporting broader educational and socio-economic outcomes in vocational ecosystems.